LabVIEW application for integrated-optics device measurement - Zhang, Jing Xiang (2010)
Almost all type of technology and engineering rely on measurement technology. Optical measurement has an edge in this field due to its high accuracy, high sensitivity and it involves no contact. Hence, this project involves the optical measurement technique consisting of two programming (LabVIEW and Matlab) and an optical measurement experiment set-up. In this project, a LabVIEW program is developed for integrated-optics device measurement that establishes communication between the tunable laser and the fiber power meter for the purpose of data acquisition for optical measurement. The developed program should demonstrate capability in the measurement of optical spectrum and real-time bistability switching of on-chip integrated optical devices. The milestone for the project will be discussed in this report. The challenges faced as well as the solutions will be touched on. The optical measurement set-up and experimental results will be also be elaborated. In conclusion, the project is a success with the objectives met. The LabVIEW programs are developed and tested on a sample (Silicon-On-Insulator). In addition, Matlab programs are developed to use the data collected from the LabVIEW to obtain the reflectivity of the sample. The experimental plots and the theoretical plots match. The resultant decrease in reflectivity of the sample, when the coupling length increases, is also consistent with the theory. The developed program will be used to support the PhD students and research staffs in Photonics Research Centre. The research fellows have tested the programs and are satisfied with them. User manuals will also be provided to them for convenience.